Pengaruh Work-Life Balance Terhadap Kinerja Karyawan Pada Hotel Four Points By Sheraton Medan - Marpaung, Selviana Meldrit Monica; Hamdani, Muhammad; Lingga, Osland Herijon (Politeknik Pariwisata Medan, 2023)
The purpose of this research is to comprehend and analyze the influence of work-life balance on employee performance at Four Points by Sheraton Medan. This study employs an associative approach method. The population for this research encompasses all employees at Four Points by Sheraton Medan, with a sample size of 51 respondents determined using the Slovin's formula. This research utilizes both primary and secondary data sources. The data analysis techniques applied in this study consist of simple linear regression analysis, the t-test of hypotheses, and the Coefficient of Determination. Data processing was conducted using SPSS (Statistical Package for the Social Sciences) software version 25.00. Based on the data analysis results, a simple regression equation model was obtained as Y = 24.164 + 0.461 X, indicating a positive influence of work-life balance on employee performance. Furthermore, from the results of the t-test analysis, a significant value of 0.002 < 0.05 was obtained, indicating that work-life balance significantly affects employee performance at Four Points by Sheraton Medan.